Functional Competency Development Strategy of Officers at Local Government Organization: กลยุทธ์การพัฒนาสมรรถนะประจำสายงานพนักงานส่วนท้องถิ่นของ องค์การปกครองส่วนท้องถิ่น - Virat, Keytapark (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
Academic Article on Strategies for Competency Development of Local Officers in Local Administrative Organization. This article aims to study the competency development of Local Administrative Organization to conform to current significant change. The objectives of this study are 1) to study the problems of competency development of local administrative officers in Local Administrative Organization 2) to plan the strategies of competency development of local administrative officers in Local Administrative Organization. The problems are found that the practical Western values ​​are inconsistent with the context of Thailand, the weakness of Thai regime, lack of freedom in administration, Intervention from political parties and executives, training and development of officers are not meet the needs in strategies of organization, lack of monitoring and evaluation also, inconsistencies of professional development. The authors then proposed 3 strategies of competency development for local officers which are 1) knowledge enhancement strategy, 2) skills development strategy, and 3) capability development strategy which require tools and assessment methods to determine the competency level of local officers then, the results of the evaluation will be used to improve the strategy for improving the competency of the local officers.